Use of Interactive and Modern Pedagogical Software in the Process of Freelancing Sites in Medicine - Vohidov Dilshod Alikulovich; Vohidov Alikul Melitoshevich (Genius Publishing Group, 2023)
Insights into these Freelancer sites and how to use them. Use of interactive and modern pedagogical software tools in the process of freelancing sites education.
Keywords: Venn and T-diagram; Freelance sites; JavaScript; Ruby